Dynamics of salt intrusion in the Mekong Delta: Results of field observations and integrated coastal-inland modelling - Eslami, Sepehr; Hoekstra, Piet; Kernkamp, Herman W. J.; Nguyen Trung, Nam; Do Duc, Dung; Nguyen Nghia, Hung; Tran Quang, Tho; Van Dam, Arthur; Darby, Stephen E.; Parsons, Daniel R.; Vasilopoulos, Grigorios; Braat, Lisanne; et al. (Earth Surface Dynamics, 2021)
On the list of challenges facing the world largest deltas, increased saline water intrusion (SWI) in the surface water system and its role in jeopardizing freshwater supply are often ranked very high. Yet, detailed process-based studies of SWI at the whole delta scale are limited, and the trends are regularly associated with global sea level rise. Here, using field measurements and a sophisticated 3D model that integrates the riverine, rural, estuarine, and coastal dynamics within one numerical domain, we study SWI at the scale of the Mekong Delta in extensive detail. While many studies downscale the SWI problem to a topic within an estuary, we show that the physical processes on the continental shelf, such as monsoon-driven ocean surge, directly influence salinity dynamics within the delta. Typical values of 20-40gcm surge over the continental shelf contribute to up to 10gkm of further SWI. The delta's estuarine system is also more sensitive than many other systems to variations of river discharge. Furthermore, spring-neap variability plays a key role in SWI in the delta. The estuarine variability from a stratified to a mixed system between neap and spring tides develops 3D processes such as estuarine circulation and tidal straining that become the main upstream salt transport mechanisms. The 3D nature of salinity dynamics, and the role of upstream and downstream processes, suggests that compromising on dimension or extent of the numerical domain can limit the accuracy of predictions of SWI in the delta. The study also showcases the fact that riverbed incision in response to anthropogenic sediment starvation in the last 2 decades has increased stratification and activated or magnified 3D salt transport subprocesses that amplify upstream salt transport. With all the external forces on the delta, namely climate change and an altered hydrological regime by the upstream dams, due to deeper estuarine channels (driven by sand mining and upstream impoundments) compared to its near past, the delta itself has become far more vulnerable to even mild natural events. This exemplifies the fundamental importance of preserving the sediment budget and riverbed levels in protecting the world's deltas against SWI.